The Contemporary world - Martinez, Rodolfo M; Pineda Jr., Reynaldo S.; Balao, Peer Sean M.; Battung, Jeffery T.; Guimpatan-Bumidang, Jamaica ; Cristobal, Joseph M.; Oyando, James Obar ; Viloria, Margie Imelda T. ; Sinuldong-Ocampo, Imelda ; Lauigan, Michelle Chan ; Esguerra, Paul ; Gumarang, Bernardo K.; Bangayan-Manera, Alma ; Maramag, Ariel M (Manila, 2018)
This new book, The contemporary world, is based on the curriculum for higher educational institutions as prepared and recommentde by the Commission on Higher Education (CHED) to be implemented starting School year 2018-2019.
Keywords: Globalization; world economics